2020
DOI: 10.3390/ijerph17165905
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel Analysis of the Relationship between Ownership Structure and Technical Efficiency Frontier in the Spanish National Health System Hospitals

Abstract: Objective: To evaluate the relationship between the ownership structure of hospitals and the possibility of their being positioned on the frontier of technical efficiency in the economic crisis period 2010–2012, adjusting for hospital variables and regional characteristics in the areas where the Spanish National Health System (SNHS) hospitals are located. Methods: 230 National Health System hospitals were studied over the two-year period 2010–2012 according to their ownership structure—public hospitals, privat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 69 publications
(106 reference statements)
1
16
0
Order By: Relevance
“…The regional average annual income per household increased the odds of reaching the efficiency frontier 6.43-fold for every one standard deviation increase in the average annual income per household. This result is in line with previous results [ 47 ], and confirms the importance of a region’s income level in improving the possibility of its hospitals’ reaching the efficiency frontier.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The regional average annual income per household increased the odds of reaching the efficiency frontier 6.43-fold for every one standard deviation increase in the average annual income per household. This result is in line with previous results [ 47 ], and confirms the importance of a region’s income level in improving the possibility of its hospitals’ reaching the efficiency frontier.…”
Section: Discussionsupporting
confidence: 93%
“…The number of private beds per thousand inhabitants decreased by 63% the odds of being positioned on the efficiency frontier. Previous work did not find this relationship significant [ 47 ], although the divergence of results is probably due to the different estimation method used. In this sense, the results of this study are more robust when using an econometric specification in line with the DEA technical efficiency density function.…”
Section: Discussionmentioning
confidence: 87%
“…This result suggests that the efficiency of the new management models would be even better if primary care units were included. This is the case of the Valencian concession model, which has recently been found to achieve better results than the traditional public management [10]. For all the management models, we find important divergences across different units.…”
Section: Discussionmentioning
confidence: 67%
“…The results obtained are mixed. For instance, the most recent study [10] concluded that PPP formulas favored hospital efficiency, while in other study the findings were inconclusive [11]. Likewise, in a previous empirical analysis focused on hospitals belonging to the Madrid Regional Health Service, the results suggest that there are no significant differences in terms of technical efficiency between public hospitals and those adopting new management formulas [12].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation